Ðžrganisation of technological safety of production on military industrial complex - O N, Andreeva (International Journal of Engineering and Technology, 2018)
The urgency of the major scientific problem of the research and development of scientific-methodical, information-analytical and software for monitoring and managing technogenic risks for electronic industry enterprises (EIE) is solved in the dissertation work, the goal and tasks of the research are determined, the main theoretical and practical results of the thesis are presented. The conceptual and terminological apparatus for monitoring and managing technogenic risks for EIE is formulated.Â Â